ON THE COMPOSITION OF HALIDE COMPLEXES OF CADMIUM EXTRACTED WITH TRIPHENYLMETHANE DYES (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The composition of the coordinatively unsaturated halide (h) complexes of cadmium in ion associates with malachite green and fuxine have been studied. The ratio of components in the complexes has been established spectrophotometrically and argentometrically and independently of nature of dyes and halides to be Cd2+:h– = 1:3. The formula of complexes is Cdh3−.
Keywords: halide complexes of cadmium; malachite green; fuxine